Assessing Disease Knowledge and Self-Management in Youth With Sickle Cell Disease Prior to Transition. (March 2019) - Speller-Brown, Barbara; Varty, Maureen; Thaniel, Lisa; Jacobs, Marni B.
Introduction: Transition of medical care from pediatrics to adult can be challenging and difficult. Until the 1970s, only half of patients diagnosed with sickle cell disease (SCD) reached adulthood. As a result of patients living longer, there is a growing need to understand factors that influence readiness to transition. This descriptive study examined age-specific SCD knowledge, self-management skills of patients, and education goals in a convenience sample of patients and their parents.Method: One hundred eighty-three transition surveys were distributed during scheduled hematology clinic visits. Surveys were analyzed with descriptive statistics to determine differences of knowledge between age groups, self-care skills, vocational supports, and educational goals. The parent group consists of children aged 0 to 4 years (32), 5 to 8 years (52), 9 to 11 years (12); the child group consists of children aged 9 to 11 years (24) and 12 to 15 years (31); and adolescent and young adult (AYA) group consists of children aged 16 to 21 years (32).Results : Indeed, 50% of parents of the 0 to 4 years age group and 33% of 5 to 8 years age group knew their child's baseline hemoglobin. Only 38% of patients aged 16 to 21 years knew their baseline hemoglobin. However, 79% of patients aged 9 to 11 years, 74% of patient aged 12 to 15 years, and 78% of AYAs could name their hematology provider. Only 66% of patients aged 16 to 21 years knew what symptoms required medical attention.Discussion: Most patients and parents had adequate basic knowledge regarding SCD. AYAs lack the disease knowledge necessary to transition care away from parents to become more independent. An assessment for transition readiness should be ongoing to include disease-specific knowledge and self-management skills.